Analysis of Software Developer Activity on a Distributed Version Control System - Shu Li; Tsukiji, Hayato; Takano, Kosuke (2016 30th International Conference on Advanced Information Networking and Applications Workshops (WAINA), 2016)
With the widespread use of distributed version control systems for software development, many software development projects are being shared and managed in a Web environment. This allows many developers, including project leaders and supporters, those who write important functions, those who resolve bugs and errors, and those who provide fundamental source code to relieve bottlenecks, to collaboratively progress their projects. In this paper, for the analysis of various characteristics of software developers, such as their skills and project roles, we present a method of feature extraction based on those developers' history of collaborative development using a distributed version control system. Real Git projects on GitHub were experimentally analyzed, and the experimental results demonstrate the feasibility of our proposed method.